PENGARUH KADAR FENOLIK PADA DAUN TEH Camelia xinensis L. TERHADAP PREFERENSI EMPOASCA SP. (Homoptera : Cicadellidae) - Saiful Saiful; Sudarsono Sudarsono (Majalah Obat Tradisional, 2013)
Phenolic compounds are secondary metabolites found in all parts of the plants aree.g.:fruits, barks, roots, and leaves of plants serve as chemical defenses as repellent against insects and herbivorous detterent. On tea leaves, the results of research gallocatechin (a derivate of catechin) was functioning known as mechanism of resistance to Empoasca sp. (Homoptera: Cicadelliadae).  The aim of this research was to know the total phenolic content of the young tea leaf  (Camelia sinensis L.) and it was to found out the effect of the phenolic compounds of preference Empoasca sp. The results obtained that the clone of “Pasir Sarongge” (PS) had total phenol content (polyphenol average ± SD) 25,69 ± 0,1 higher than Kiara clone 18,47 ± 0,13.  The higher the polyphenol in the young tea leaf bud could be act as Empoasca sp. Detterent.